Prior Knowledge, Creativity and Entrepreneurial Alertness of Undergraduate Students in Ogun State-Owned Universities - Olatoye, Adeolu Oludare; Dosunmu, Margaret Moronke; Bukki, Abolaji O. (NIU Journal of Social Sciences; Vol 6 No 2 (2020): KIU Journal of Social Sciences, Vol. 6 No. 2, June 2020, 2020)
This research examined prior knowledge, creativity, and entrepreneurial alertness of undergraduate students in Ogun State-Owned Universities, Nigeria. A descriptive survey design was adopted for the study. Six hundred (600) respondents were selected as the sample for this study. The respondents were randomly drawn from four (4) Faculties (Faculty of Science, Faculty of Arts, Faculty of Education, Faculty of Administrations and Management Science. Prior knowledge to the business questionnaire, Creativity questionnaire, and Entrepreneurial alertness scale were used as instruments for data collection. The statistical methods of analysis used for testing the raised research questions were independent t-test and regression analysis at 0.05 level of significance. Findings revealed that there Prior knowledge of entrepreneurship and creativity had a significant influence on entrepreneurial alertness of undergraduate students. It was recommended among others that more activities will provide opportunities to gain authentic experience that will create bridges between the knowledge gained and the application of that knowledge in practice should be enforced in our tertiary institutions. Keywords : Prior Knowledge, Creativity, Entrepreneurial Alertness, Opportunity recognition and Undergraduates